2016
DOI: 10.1177/2057158516662431
|View full text |Cite
|
Sign up to set email alerts
|

The TECS model leads to active use of technology in home care

Abstract: Digitization in healthcare is accelerating worldwide. This article focuses on the X-Changery development project involving home-care nurses and their use of the iPad as a new tool in patients' homes. The goal of the project was to bring knowledge from recent research on technological literacy in working life back to a work setting, thus giving nurses new technology competencies with the aim of enhancing their professionalism through the use of the iPad as a work tool. Through field observations, learning labs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Interviews were conducted in the homes of participants living in a greater municipality of the Capital Region of Denmark, where nurses participated in a development project involving the mandatory use of iPads (Apple Computer, Cupertino, CA) as a tool in their daily work. 6 The municipality employed 30 nurses, all of whom were involved in the project. They used iPads for multiple purposes, such as documenting, taking pictures, and ordering and dealing with medicines, as entry keys for the homes they visited, looking up and retrieving information, and the like.…”
Section: Methodsmentioning
confidence: 99%
“…Interviews were conducted in the homes of participants living in a greater municipality of the Capital Region of Denmark, where nurses participated in a development project involving the mandatory use of iPads (Apple Computer, Cupertino, CA) as a tool in their daily work. 6 The municipality employed 30 nurses, all of whom were involved in the project. They used iPads for multiple purposes, such as documenting, taking pictures, and ordering and dealing with medicines, as entry keys for the homes they visited, looking up and retrieving information, and the like.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of technological literacy in the adaptation of prospective elementary school teachers' scientific reasoning from civic science is a form of new habits towards technology. Relevant to this, Gars and Skov (2016) clarify that technology creates new habits and routines for individuals. Technological literacy implies the active use of technology in society.…”
Section: Technology Literacy As Elementary School Education Problems Of Studentsmentioning
confidence: 96%
“…We classified the selected studies in five groups, according to the main purpose of ICT use by health care aides: (1) improve everyday work (n ¼ 12, 30%), 46,[51][52][53][54][55][56][57][58][59][60][61] (2) access electronic health records for home care (n ¼ 9, 22.5%), [62][63][64][65][66][67][68][69][70] (3) facilitate client assessment and care planning (n ¼ 9, 22.5%), [71][72][73][74][75][76][77][78][79] (4) enhance communication (n ¼ 7, 17.5%), 2,40,80-83 and (5) provide care remotely (n ¼ 3, 7.5%). 35,84,85 Fig.…”
Section: Study Purposementioning
confidence: 99%
“…56,64,71,84 Some studies reported incomplete hardware features as a significant barrier to adopting and implementing ICT. 56,65,77,86 Time-consuming adoption and implementation was another significant barrier for health care aides, 2,35,40,51,53,55,56,59,[63][64][65]85 This further amplifies the need for communication with ICT providers in order for an effective ICT solution. 71,72,76 In some studies, users reported the ICT implementation process as time consuming.…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation